Pengaruh Keterlibatan Kerja, Budaya Organisasi dan Motivasi Kerja Terhadap Kepuasan Kerja Pegawai Pada Kantor Kecamatan Pesantren - Dila Rizky Amanda; Zaenul Muttaqien; Agung Pambudi Mahaputra (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of work involvement, organizational culture, and work motivation on employee job satisfaction at the Pesantren District Office, Kediri City. The type of research used is quantitative research with a survey method, using a questionnaire as the main instrument. The population in this study consists of all employees at the Pesantren District Office, totaling 30 people, with a saturated sampling technique so that the entire population was used as the research sample. Data analysis in this study was carried out using multiple linear regression, t-test, F-test, and the coefficient of determination (R²) to determine the partial and simultaneous effects of each independent variable on the dependent variable. The results of this study indicate that work involvement, organizational culture, and work motivation, both partially and simultaneously, have a positive and significant effect on employee job satisfaction. These findings emphasize the importance of enhancing employee involvement, building a conducive organizational culture, and strengthening work motivation to create a harmonious work environment and improve overall organizational performance.